2021
DOI: 10.18805/ajdfr.dr-1592
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Dietary Supplementation of Linseed Oil and Natural Antioxidants on Production Performance, Fatty Acid Profile and Meat Lipid Peroxidation in Broilers

Abstract: Background: Healthy omega-3 fatty acid (n-3FA) enriched poultry meat can be achieved through dietary supplementation of n-3 FA rich feed ingredients like fish meal, linseed, linseed oil, marine algae, etc to broiler birds. A study was conducted to investigate the effect of supplementing linseed oil (LO) in combination with natural antioxidants like curry leaf powder, ginger powder and turmeric powder to explore the additional benefits of these natural antioxidants in reducing meat lipid peroxidation. Methods: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 23 publications
1
5
0
Order By: Relevance
“…Petri dishes were incubated at 10 °C for 7 days. The number of microbial bacteria is expressed as log cfu/g [ 28 , 29 ].…”
Section: Methodsmentioning
confidence: 99%
“…Petri dishes were incubated at 10 °C for 7 days. The number of microbial bacteria is expressed as log cfu/g [ 28 , 29 ].…”
Section: Methodsmentioning
confidence: 99%
“…In the breast muscle, no difference (p > 0.05) in PUFA content was observed between treatment groups. Similarly, studies have shown no variation in breast PUFA in broiler chickens fed with flaxseed/linseed oil along with 0.5% of curry leaf, ginger or turmeric powders [88], 5-12.5% turmeric powder [23], and 2 g sweet chestnut tannins [77].…”
Section: Fatty Acid Contents Of Raw Breast Musclementioning
confidence: 98%
“…Fats and oils not only help to improve the quality of feed, but they also reduce the amount of dust produced by dry feed materials and thus increase digestibility and physiological terms fats are important in the formation of the cell membrane [12]. Vegetable oils are often used as a high-energy food in the nutrition of broilers, as it is noted that broilers that are fed on diets containing vegetable oils, including flax oil, perform better than those that feed on diets without including oil [13]. Flaxseed oil is one of the richest dietary sources of the essential fatty acid linolenic [14].…”
Section: Introductionmentioning
confidence: 99%